2017
DOI: 10.1016/j.foodcont.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

An initial characterization of aflatoxin B1 contamination of maize sold in the principal retail markets of Kigali, Rwanda

Abstract: 24Food security considerations have shifted in recent years, with the recognition that available food 25 should also be nutritious and safe. There is a growing evidence base for contamination of maize 26 and other crops by fungal toxins in the tropics and sub-tropics. As an initial snapshot of 27 contamination by one of these toxins in Rwanda, Aflatoxin B1 (AFB1) was analyzed in 684 28 samples of maize flour collected in seven principal retail markets of Kigali and in 21 samples of 29 animal feed from seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…Rapid and early detection is important for prompt intervention. Current detection methods include high-performance liquid chromatography (HPLC), Enzyme Linked Immunosorbent Assay ELISA, fluorometric assays and lateral flow assays [16][17][18][19]. However, these methods are invasive, require specialised skills and are weak for real time assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid and early detection is important for prompt intervention. Current detection methods include high-performance liquid chromatography (HPLC), Enzyme Linked Immunosorbent Assay ELISA, fluorometric assays and lateral flow assays [16][17][18][19]. However, these methods are invasive, require specialised skills and are weak for real time assessments.…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that mycotoxin and microbiological contamination, as well as the presence of pesticides, represent an unacceptable risk for this vulnerable population. The problem of high aflatoxin levels lies not only in the fungal‐promoting weather conditions of Africa (Clay & Dejaegher, ) but also in the lack of awareness of mycotoxin contamination risks (Nishimwe, Wanjuki, Karangwa, Darnell, & Harvey, ).…”
Section: Discussionmentioning
confidence: 99%
“…The high susceptibility of maize products to aflatoxins in our study is consistent with existing literature and highlights the need for deliberate action to ensure food safety in infant products. Two previous studies provided information on mycotoxin levels in products available in the Kigali market (Matsiko et al, ; Nishimwe et al, ). More than 680 maize flours were analysed in the study of Nishimwe et al (), showing total aflatoxin levels generally above tolerable limits set by the European Commission (4 μg/kg; European Commission, ), the Kenyan Government, and the United Nations World Food Programme (10 μg/kg; International Food Programme Research Institute, ) and the U.S. Food and Drug Administration (20 μg/kg; U.S. Food and Drug Administration, ) for maize products.…”
Section: Discussionmentioning
confidence: 99%
“…More than 90% (92.7%) of the respondents did not know the term "aflatoxin" and were not aware of the problem of toxins, even not in their local language Kinyarwanda. These findings clearly have shown that there is a need to create awareness on AF among the Rwandese by training to prevent food colonization by mycotoxigenic fungi [36]. Ignorance on the understanding of AF, and conditions in which producing fungal species grow, could lead to acute and chronic toxicity [37], and subsequent AF outbreaks [13,38].…”
Section: Soybean Pre-and Post-harvest Handlingmentioning
confidence: 99%
“…Aflatoxin contamination of maize can be a problem, similar to reports from other countries in the region. Maize in principal retail markets in Rwanda was found to be contaminated by aflatoxin (2-35% and 66-100% of samples were above the US and EU limits, respectively) with AF up to 26 µg/kg [36]. A three-year survey done on soybean in America, Europe, Asia and Oceania on the mycotoxins occurrence in feed proved that soybean was mostly contaminated by FB (range, 12 µg/kg -2,966 µg/kg) [58].…”
Section: Multi Mycotoxins In Soybeanmentioning
confidence: 99%